2020
DOI: 10.1038/s41421-020-00214-5
|View full text |Cite
|
Sign up to set email alerts
|

Global immune characterization of HBV/HCV-related hepatocellular carcinoma identifies macrophage and T-cell subsets associated with disease progression

Abstract: Diverse immune cells in the tumor microenvironment form a complex ecosystem, but our knowledge of their heterogeneity and dynamics within hepatocellular carcinoma (HCC) still remains limited. To assess the plasticity and phenotypes of immune cells within HBV/HCV-related HCC microenvironment at single-cell level, we performed single-cell RNA sequencing on 41,698 immune cells from seven pairs of HBV/HCV-related HCC tumors and non-tumor liver tissues. We combined bio-informatic analyses, flow cytometry, and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 47 publications
4
126
0
Order By: Relevance
“…In tumor tissues, regulatory T cells (Tregs) undergo abnormal changes in expression, such as the change in LAG3 expression observed in classic Hodgkin lymphoma, upregulated LAYN expression in FOXP3 + Helios + Tregs, and changes in CCR8 and IL1R2 expression in HCC [ 134 , 135 ]. In addition, the chronic remodeling of tumor antigens alters Treg cell frequencies and subsequently promotes the recurrence of HCC [ 136 , 137 ].…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…In tumor tissues, regulatory T cells (Tregs) undergo abnormal changes in expression, such as the change in LAG3 expression observed in classic Hodgkin lymphoma, upregulated LAYN expression in FOXP3 + Helios + Tregs, and changes in CCR8 and IL1R2 expression in HCC [ 134 , 135 ]. In addition, the chronic remodeling of tumor antigens alters Treg cell frequencies and subsequently promotes the recurrence of HCC [ 136 , 137 ].…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
“…To the best of our knowledge, TAMs undergo polarized activation upon distinct exposure. Some single-cell sequencing studies demonstrated that the classically activated (M1) macrophage signature and alternatively activated (M2) macrophage signature could coexist in single macrophages, thus identifying various subsets of myeloid cells [ 136 , 149 ]. Apart from the traditional M1/M2 activation paradigm in macrophages, scRNA-seq has revealed the complexity of macrophage expression profiling.…”
Section: Applications Of Single-cell Sequencing In Cancer Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, hepatic macrophages promote HCC development by producing TNF-α and IL-6 [ 151 ]. CCL18 + M2 macrophages present in the tumors of advanced HCC promote angiogenesis, tumor invasion, metastasis, and associate with poor prognosis [ 152 ]. Hence, monocytes and macrophages play a key role in the immunopathogenesis of HBV infection.…”
Section: Involvement Of Innate and Adaptive Immune Cells In The Development Of Fibrosis Cirrhosis And Hccmentioning
confidence: 99%
“…5d). Indeed, we observed that, SPP1 + macrophages, which have been reported in colon cancer and closely interact with cancer-associated broblasts (CAFs) 22 , were more in ltrated in S100P-SPP1+ iCCA pps , while CCL18 + macrophages, which were abundant in advanced hepatocellular carcinoma 23 , were mostly in ltrated in S100P+SPP1-iCCA phl (Fig. 4c, d).…”
Section: Molecular Pro Les and Transcription Network Of S100p+spp1-and S100p-spp1+ Iccasmentioning
confidence: 79%